The receptive vocabulary of Spanish 6th-grade primary-school students in CLIL instruction: A preliminary study - Andrés Canga Alonso (Universidad de La Sabana, 2013)
One of the key factors in early stages of L2 learning is the number of words learners know. However, there has been little research regarding the receptive vocabulary size of learners involved in content and language integrated learning (CLIL) programmes at primary level. Accordingly, the 2,000-word frequency band of the Vocabulary Levels Test (VLT) (Schmitt, Schmitt, & Clapham, 2001) was administered to explore the receptive vocabulary knowledge of 6th-grade, primary-level Spanish students learning English through CLIL instruction to relate their receptive vocabulary size to their ability to understand written and spoken discourse in English and to establish sex-based differences amongst the participants. The results show that students' receptive vocabulary knowledge is below the 1,000 frequency band, which implies that students may find it difficult to understand spoken and written discourse in English (Laufer, 1992; Nation, 2001; Adolphs & Schmitt, 2004). As for sex-based differences, female students outscored their male partners in the VLT, but these differences were not statistically significant. Nevertheless, further research needs to be conducted with a larger sample of CLIL learners to compare groups from different schools implementing these programmes in the same area, as well as to compare their results with those obtained by students in traditional non-CLIL environments.